2011
DOI: 10.1039/c0sm00936a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lens epithelial cell growth via immobilisation of hyaluronic acid on atmospheric pressure plasma modified polystyrene

Abstract: Naturally occurring macromolecules have the potential for providing non-fouling coatings on substrates based on a steric entropic principle. In order for this effect to occur, the macromolecules that adhered to the surface must have the correct chemical conformation. This article reports on the immobilisation of hyaluronic acid (HA) onto polystyrene substrates for the purpose of repelling cellular adhesion thereon. In order to create a polystyrene surface capable of adhering HA in the required orientation subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 59 publications
4
16
0
Order By: Relevance
“…For our hyaluronized silicon surfaces made at the NaHA concentration of 1.2 mg ml −1 , XPS used under the same conditions as for dextran showed the ratio of C to N on average to be 10.8 (streptococcus zooepidemicus NaHA), 11.2 (human NaHA), and 11.4 (rooster comb NaHA). These values are all consistent with XPS results for HA films determined in chemisorptions experiments (D'Sa et al 2011; Suh et al 2005). Given that the ellipsometric data presented in Figure 2 indicate the HA films to be much thicker than the 2.5 nm detection depth used, it is unlikely that these measurements include interference from other chemical constituents present.…”
Section: Surface Preparationsupporting
confidence: 89%
See 1 more Smart Citation
“…For our hyaluronized silicon surfaces made at the NaHA concentration of 1.2 mg ml −1 , XPS used under the same conditions as for dextran showed the ratio of C to N on average to be 10.8 (streptococcus zooepidemicus NaHA), 11.2 (human NaHA), and 11.4 (rooster comb NaHA). These values are all consistent with XPS results for HA films determined in chemisorptions experiments (D'Sa et al 2011; Suh et al 2005). Given that the ellipsometric data presented in Figure 2 indicate the HA films to be much thicker than the 2.5 nm detection depth used, it is unlikely that these measurements include interference from other chemical constituents present.…”
Section: Surface Preparationsupporting
confidence: 89%
“…Park et al (Park et al 2003) found that fibroblasts did not spread on HA-containing gel surfaces. Polystyrene surfaces modified via immobilization of hyaluronic acid have been shown to resist attachment of human lens epithelial cells for application in ocular medicine (D'Sa et al 2011). Patterned surfaces of dextran and HA show preferential attachment of macrophages to the dextranized regions (Tsai et al 2011b).…”
Section: Resultsmentioning
confidence: 99%
“…For example, treating IOL surface with plasma or immobilizing with heparin, poly(ethylene glycol), or phosphorylcholine can reduce the bioadhesion better than coating with inert materials. [11][12][13][14][15][16] However, bioadhesion can still be found on coated hydrophilic surfaces, which may be due to the undesired surface coating by common hydrophilic molecules. A more effective antifouling coating is essential for IOL surface modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have studied the effects of changing surface chemistry with the addition of various functional groups such as amine, carboxyl and hydroxyl groups, to encourage cell attachment in various cell types [78][79][80]. The cellular response could also be controlled by incorporating ECM molecules such as glycosaminoglycan [70,81,82].…”
Section: Cornea and Conjunctivamentioning
confidence: 99%
“…One method that has been investigated to alleviate PCO is surface modification of IOLs to control the cellular response [57, [70][71][72][73]. It is widely known that material properties such as the surface chemistry, wettability and roughness can affect the cellular response [74][75][76][77].…”
Section: Cornea and Conjunctivamentioning
confidence: 99%